MottCalc: A new tool for calculating Mott scattering differential cross sections for analytical purposes - Maragkos, Fotis; Kokkoris, Michael; Lagogiannis, Anastasios (HNPS Advances in Nuclear Physics, 2020)
In the last few years, the popularity of ERDA applications has soared along with the implementation of time of flight (TOF) type measurements. However, ERDA and other forward scattering IBA techniques suffer from the possibility of the occurence of Mott scattering. This leads to deviations in the elastic differential cross sections which in turn demand special care in the treatment of the obtained experimental spectra. To address this issue, a new code has been developed, called MottCalc (Mott Calculator). Based on the analytical formula, first developed by Mott, which describes the phenomenon, the code is capable of producing theoretical angular and energy distributions of such differential cross sections along with the appropriate R33 files, which in turn can be implemented in all the widely used analytical codes (SIMNRA, DF, POTKU etc.). The electronic screening effect is taken into account in these calculations by implementing the Andersen model. A list of 314 different isotopes is available to choose from as projectile and target nuclei. The list can be expanded with radioactive isotopes. The program is available in two distinct versions, an Excel Spreadsheet and a stand-alone application. Both versions of the program can be freely downloaded from the webpage of the Nuclear Physics group of NTUA (nuclearphysics.ntua.gr/downloads.php). The implementation of the code as well as the features and capabilities of both versions of the program are presented in the current work along with a brief synopsis of the elastic Mott scattering phenomenon.